BIOENHANCED TOCOTRIENOL-RICH VITAMIN E (TOCOVID) IMPROVES NERVE CONDUCTION VELOCITY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: PHASE II DOUBLE-BLIND, RANDOMIZED CONTROLLED CLINICAL TRIAL - Chuar, Pei Fen; Ng, Yeek Tat; Phang, Sonia Chew Wen; Koay, Yan Yi; Ho, J-Ian; Ho, Loon Shin; Henien, Nevein Philip Botross; Ahmad, Badariah; Kadir , Khalid Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION This study aims to investigate the effects of bioenhanced tocotrienol-rich vitamin E (Tocovid SuprabioTM) on nerve conduction parameters and serum biomarkers among patients with type 2 diabetes mellitus. METHODOLOGY Eighty-eight patients were randomized to receive 200 mg of tocotrienol-rich vitamin E (Tocovid) twice daily or matching placebo for 12 months. Nerve conduction parameters, vitamin E levels and serum biomarkers were measured at 2, 6 and 12 months. RESULTS After 12 months, patients in the Tocovid group showed highly significant improvement in conduction velocity (CV) of both median and sural sensory nerves compared to placebo. The between intervention group differences (treatment effect) in CV were 1.60 m/s (95% CI: 0.70, 2.40, p=0.007) for median nerve and 1.97 m/s (95% CI: 1.10, 3.45, p=0.036) for sural nerve. Significant improvement in CV was only observed up to six months in tibial motor nerve CV, 1.30 m/s (95% CI: 0.60, 2.20, p<0.001). There were no significant changes in transforming growth factor beta1 (TGFÎ²-1) and vascular endothelial growth factor A (VEGF-A). After six months of washout, there were no significant differences from baseline between groups in all nerve conduction parameters of all three nerves. CONCLUSION Tocovid at 200 mg twice a day significantly improved median and sural sensory nerve CV at 12 months but improvement in tibial motor nerve CV was only observed up to six months. All improvements diminished after six months of washout.